Peran Guru Pendidikan Agama Islam dalam Membentuk Karakter Religius Siswa - Hazizah Isnaini (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
Moral education today is very worrying and declining. Many behaviors violate immorality, causing chaos for oneself and public unrest. The development of modern science and technology has caused moral values ​​to be neglected due to a lack of cultivation and practice of moral learning. Strengthening character is considered important in overcoming moral problems amidst the complexity of social life. Seeing the survival of a nation can be seen from the character of a nation. Islamic Religious Education Teachers do not just teach but must be able to develop moral norms or character in their students and have a big responsibility in forming students' religious character. They act as facilitators, leaders and role models for students in understanding, practicing and internalizing the teachings of the Islamic religion. Islamic religious and moral learning is focused on building character with full compassion for all elements of the universe. This research is qualitative research with a descriptive approach, researchers carry out research in the field by making observations. The aim to be achieved in this research is to determine the role of PAI teachers in shaping students' religious character.